PENGARUH STRUKTUR MODAL, PROFITABILITAS, LIKUIDITAS, UKURAN PERUSAHAAN DAN GROWTH OPPORTUNITY TERHADAP NILAI PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2014-2016) - Dhian Septiara, 14.05.52.0136; Nurhayati, Ida (Students' Journal of Accounting and Banking, 2018)
The purpose of this study to test the effect of disclosure of structure, probability, liquidity size and growth opportunity to the firm value on manufacturing companies listed in Indonesia Stock Exchange 2014-2016.Data usedin this research issecondary data,the data in this study were obtained from the Anuat Report (AR) 2014-2016. This study was conducted using a sample of 198 companies listed on the stock exchange in 2014-2016. Methods of sample selection using purposive sampling and analysis model used is multiple linear regression. The result of the research shows that disclosure of structure (DER) variable has negative and significant influence to the firm value (PBV), whereas probability (ROE) variable has positive and significant influence to the firm value (PBV), whereas liquidity (CR) has no effect on firm value (PBV,) whereas Size variable has positive and significant influence to firm value (PBV), and growth opportunity variable has positive and significantinfluence to firm value (PBV).Keywords: structure, probability,liquidity, size, growth opportunity, firm value